PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA MATERI TEOREMA PYTHAGORAS KELAS VIII DI SMP - Sahat Benaya; Tria gustiningsi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics results in junior high schools are usually not very good as teaching usually focuses on the teacher, so limiting their participation in learning. This study aimed to find out how the Jigsaw collaborative learning approach affects pupils' math achievement on the Pythagorean Theorem subject. Using a quantitative approach, the study included only a post-test for the control group in a quasi-experimental design. All the participants were eighth graders at SMP Negeri 26 Jambi City in the 2025–2026 academic year. With a total of 60 pupils, students were picked using cluster random sampling, therefore one class learned via the Jigsaw approach and another got Direct Instruction. A math test helped to collect the data that was then analyzed with both descriptive and inferential statistics. The normality test revealed that both groups exhibited a normal distribution; the homogeneity test confirmed comparable variances. The independent samples t-test revealed a significant difference between the experimental and control groups (t = 3.555, p < 0.001). Students who learned using the Jigsaw approach had an average score of 83.30, whereas those who received Direct Instruction had an average score of 76.77. These findings point to a major rise in math performance among pupils using the Jigsaw approach of collaborative learning. So, particularly in learning the Pythagorean Theorem, the Jigsaw approach might be seen as a useful substitute teaching approach for improved learning outcomes.